Exercise training restores weight gain and attenuates hepatic inflammation in a rat model of non‐celiac gluten sensitivity. Issue 4 (15th February 2023) - Pauli, José R.; Muñoz, Vitor R.; Vieira, Renan Fudoli Lins; Nakandakari, Susana C. B. R.; Macêdo, Ana Paula Azevêdo; de Lima, Robson Damasceno; Antunes, Gabriel Calheiros; Simabuco, Fernando M.; da Silva, Adelino Sanchez Ramos; de Moura, Leandro P.; Ropelle, Eduardo R.; Cintra, Dennys E.; et al.
Abstract: Gluten intolerance is associated with several disorders in the body. Although research has grown in recent years, the understanding of its impact on different tissues and the effects of physical exercise in mitigating health problems in the condition of gluten intolerance are still limited. Therefore, our objective was to test whether gliadin would affect metabolism and inflammation in liver tissue and whether aerobic physical exercise would mitigate the negative impacts of gliadin administration in rodents. Wistar rats were divided into exercised gliadin, gliadin, and control groups. Gliadin was administered by gavage from birth to 60 days of age. The rats in the exercised gliadin group performed an aerobic running exercise training protocol for 15 days. At the end of the experiments, physiological, histological, and molecular analyzes were performed in the study. Compared to the control group, the gliadin group had impaired weight gain and increased gluconeogenesis, lipogenesis, and inflammatory biomarkers in the liver. On the other hand, compared to the gliadin group, animals in the exercise‐gliadin group had a recovery in body weight, improved insulin sensitivity, and a reduction in some gluconeogenesis, lipogenesis, and inflammatory biomarkers in the liver. In conclusion, our results revealed that the administration of gliadin from birth impaired weight gain and induced an increase in hepatic inflammatory cytokines, which was associated with an impairment of glycemic homeostasis in the liver, all of which were attenuated by adding aerobic exercise training in the gliadin group.